Manajemen Pembelajaran Di Pesantren Miftahul Ulum Bettet Pamekasan Pada Masa Pandemi Covid-19 - Moh. Subhan; Ahmad (State Islamic Institute of Madura, 2021)
Abstract: The Covid-19 pandemic has an impact on all aspects of human life, including education. All educational units generally carry out online learning to avoid the spread of the virus. However, the Miftahul Ulum Bettet Pamekasan Islamic Boarding School still conducts offline learning but still enforces strict health protocols. This study seeks to reveal the learning management applied by the cottage during the Covid-19 pandemic. The research method used is a qualitative approach with the type of case study. The results of this study indicate that the management carried out includes 3 things; 1) planning related to the fulfillment of health protocols and planning related to the mechanism of the learning process contained in the lesson plans and syllabus; 2) the implementation of learning is carried out face-to-face while still paying attention to the health protocol. The implementation of learning includes three stages, namely introduction, core activity, and closing; 3) evaluation is carried out continuously at the end of the lesson in order to see the level of learning effectiveness. In addition, the evaluation of learning is also carried out with a summative and formative evaluation model.